Detection of FLT3-ITDMutation in Twenty ChildwithAcuteMyeloidLeukemia in One Iraqi Teaching Hospital - Dhahir, Ethar k.; Al-Mudallel, Subh S.; Dhahi, Maysaa A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background:Pediatric acute myeloid leukemia (AML) has a poor prognosis, and novel therapies are needed. The FLT3 tyrosine kinase inhibitorsrepresents a promising target in pediatric AML. Objectives:This study was done to estimate the frequency of FLT3- ITD mutation in childhood acute myeloid leukemia using conventional PCR & correlate this mutation with the clinical presentation and response to induction therapy. Patients, Materials &Methods: Twenty children with AML, and 16 children with reactive bone marrow as negative control were enrolled in this study. Those patients were attending Child Welfare Teaching Hospital in Baghdad from March 2010 to July 2011 .For each patient hematological investigations including complete blood picture, and bone marrow aspiration were done.FLT3-ITD mutation was detected by conventional PCR technology using specific primers. Complete hematological remission achievement after induction chemotherapy was assessed by clinical examinations and full laboratory investigations. Results: Out of 20 AML children who participated in this study, 2 (10%) had FLT3-ITD mutation. The mean age of patients who had the mutation was higher than those without the mutation; and the mutated patientswere males, (P> 0.05).The FLT3-ITD mutation showed no correlation to clinical presentation.The peripheral blood & bone marrow blast cell percent werenon significantly higherin mutated patients as compared to non mutated patients. Regardingits relation to FAB classification, the FLT3-ITD mutation was only detected in M3(1/20) and M3v(1/20), and no mutation was found in other subtypes(M1,M2,M5). Furthermore, mutated patients showed lower response to inductiontherapy as compared to non mutated patients. Conclusions: This is a noval study in one Iraqi teaching hospital to detect FLT3-ITD mutation by using conventional PCR in children with AML. This mutation was detected in 10% of thosechildren , and since they were male,older age group,and presented with higher peripheral blood &bone marrow blast cell percent thus we may propose that it may be used as a marker for the aggressiveness of the disease and can be used to modulate the treatment strategy for those patients.